Isolation of compounds from the roots of Ambrosia artemisiifolia and their effects on human cancer cell lines - Ferencz Elek (ZEITSCHRIFT FÜR NATURFORSCHUNG C-A JOURNAL OF BIOSCIENCES, 2023)
Common ragweed (Ambrosia artemisiifolia L.) is an invasive plant in Europe with spreading use in the contemporary folk medicine. The chemical composition of the above-ground parts is extensively studied, however, the metabolites of the roots are less discovered. By multiple chromatographic purification of the root extracts, we isolated thiophene A (1), n-dodecene (2), taraxerol-3-O-acetate (3), α-linoleic acid (4), (+)-pinoresinol (5), and thiophene E (7,10-epithio-7,9-tridecadiene-3,5,11-triyne-1,2-diol) (6). The 1H NMR data published earlier for 1 were supplemented together with the assignment of 13C NMR data. Thiophene E (6), which is reported for the first time from this species, exerted cytotoxic and antiproliferative effects on A-431 epidermoid skin cancer cells, whereas taraxerol-3-O-acetate (3) and α-linoleic acid (4) had slight antiproliferative effect on gynecological cancer cell lines. Thiophene E (6) and taraxerol-3-O-acetate (3) displayed antiproliferative and cytotoxic effects on MRC-5 fibroblast cells. Thiophene E (6) exerted weak antibacterial activity (MIC 25 μg/mL) on MRSA ATCC 43300, on Staphylococcus aureus ATCC 25923, Escherichia coli AG100 and E. coli ATCC 25922 both thiophenes were inactive. Although the isolated compounds exerted no remarkable cytotoxic or antiproliferative activities, the effects on MRC-5 fibroblast cells highlight the necessity of further studies to support the safety of ragweed root.